Do People with Type 2 Diabetes Think They are Unhealthy? A Cross-Sectional Study in Celaya, Mexico - Karla C. Paz-Salinas; Nicolas Padilla-Raygoza; Silvia C. Delgado-Sandoval; Georgina Olvera-Villanueva; Ma Laura Ruiz-Paloalto (University Library System, University of Pittsburgh, 2015)
Background: Type 2 diabetes is a chronic disease that presents a significant burden on health care systems in many countries. With the rise of obesity, the incidence of Type 2 diabetes has also been steadily increasing. A healthy lifestyle and understanding of diabetes management are important factors for delaying the onset of comorbidities associated with Type 2 diabetes. The objective of this study was to evaluate the self-perception of health in individuals with Type 2 diabetes as it relates to BMI status, which has important implications for the implementation of preventive programs. Methods: A cross-sectional lifestyle survey was implemented in the region of Celaya, Guanajuato, Mexico, targeting 100 participants diagnosed with Type 2 diabetes. Anthropometric measurements and participant characteristics were also obtained. Fisher's exact test was used to determine if the proportions of lifestyles perceptions differed by BMI status. Results:  Participants had a mean age of 56.12 ± 10.26, a mean BMI of 29.13 ± 5.48 kg/m2, were mostly married (67.0%), and female (70.0%). None of the normal weight participants perceived themselves as unhealthy. 95% of overweight/obese participants perceived themselves to be healthy, despite a diagnosis of diabetes and being overweight/obese, while only 5% perceived themselves to be unhealthy. However, these differences in the perceptions of health classified by BMI status were not statistically significant (p = 0.42). Conclusion: Our findings indicate that overweight and obese persons with Type 2 diabetes in Celaya, Mexico may have misperceptions about their own health, even though these findings were not statistically significant. These preliminary data highlight the importance of implementing prevention and educational programs among those with diabetes, in order to combat health misperceptions and raise awareness about the dangers of diabetes and obesity. Furthermore, more research with larger sample sizes is needed  in order to fully understand the effects of perception of health on actual health.